World health day - 7th april, 2004 "road safety is no accident" - Saxena, S C (Indian Journal of Community Health, 2004)
In 1948, the First World Health Assembly called for the creation of a "World Health Day". Since 1950, World Health Day has been celebrated on the 7th of April of each year. The objective of World Health Day is to raise global awareness of a specific health theme to highlight a priority area of concern for the World Health Organization (WHO). The Day serves as a launch for a long-term advocacy program for which activities will be undertaken and resources provided well beyond 7th April. To Celebrate the theme of this year "Road Safety is No accident", on 7th April 2004 around the globle, hundreds of organizations hosted events to help raise awareness about road traffic injuries, their grave consequences and enormous casts to society. They also contributed to spreading the message that such injuries can be prevented. In 1948, the First World Health Assembly called for the creation of a "World Health Day". Since 1950, World Health Day has been celebrated on the 7th of April of each year. The objective of World Health Day is to raise global awareness of a specific health theme to highlight a priority area of concern for the World Health Organization (WHO). The Day serves as a launch for a long-term advocacy program for which activities will be undertaken and resources provided well beyond 7th April. To Celebrate the theme of this year "Road Safety is No accident", on 7th April 2004 around the globle, hundreds of organizations hosted events to help raise awareness about road traffic injuries, their grave consequences and enormous casts to society. They also contributed to spreading the message that such injuries can be prevented. The accident is defined as unexpected, unplanned event envolving injury, disability or death. The accidents occur in almost all countries. The most alarming fact is that accidents kill more young trained adults between 15-24 years of age group of males, mainly among two wheelers. All sorts of accidents kill more than 5 million people a year in whole of world including about 9 lakh deaths from road accidents alone, The road accidents rank fourth in order among the leading causes of death and are responsible for approximately & parcent of all deaths in the world. For every death, there are as many as 30-40 minor enjuries and IQ- 15 serious injuries requring long periods of expensive care, nursing and Treatment.